Altered muscle mitochondrial, inflammatory and trophic markers, and reduced exercise training adaptations in type 1 diabetes. (24th January 2022) - Minnock, Dean; Annibalini, Giosuè; Valli, Giacomo; Saltarelli, Roberta; Krause, Mauricio; Barbieri, Elena; De Vito, Giuseppe
Abstract : Abstract: Growing evidence of impaired skeletal muscle health in people with type 1 diabetes points toward the presence of a mild myopathy in this population. However, this myopathic condition is not yet well characterised and often overlooked, even though it might affect the whole‐body glucose homeostasis and the development of comorbidities. This study aimed to compare skeletal muscle adaptations and changes in glycaemic control after 12 weeks of combined resistance and aerobic (COMB) training between people with type 1 diabetes and healthy controls, and to determine whether the impaired muscle health in type 1 diabetes can affect the exercise‐induced adaptations. The COMB training intervention increased aerobic capacity and muscle strength in both healthy and type 1 diabetes sedentary participants, although these improvements were higher in the control group. Better glucose control, reduced glycaemic fluctuations and fewer hypoglycaemic events were recorded at post‐ compared to pre‐intervention in type 1 diabetes. Analysis of muscle biopsies showed an alteration of muscle markers of mitochondrial functions, inflammation, ageing and growth/atrophy compared to the control group. These muscular molecular differences were only partially modified by the COMB training and might explain the reduced exercise adaptation observed in type 1 diabetes. In brief, type 1 diabetes impairs many aspects of skeletal muscle health and might affect the exercise‐induced adaptations. Defining the magnitude of diabetic myopathy and the effect of exercise, including longer duration of the intervention, will drive the development of strategies to maximise muscle health in the type 1 diabetes population. Key points: Type 1 diabetes negatively affects skeletal muscle health; however, the effect of structured exercise training on markers of mitochondrial function, inflammation and regeneration is not known. Even though participants with type 1 diabetes and healthy control were comparable for cardiorespiratory fitness ( V ̇ O 2 max ${\dot{V}_{{{\rm{O}}_{\rm{2}}}{\rm{max}}}}$ ) and muscle strength at baseline, molecular markers related to muscle health were decreased in type 1 diabetes. After training, both groups increased V ̇ O 2 max ${\dot{V}_{{{\rm{O}}_{\rm{2}}}{\rm{max}}}}$ and muscle strength; however, a larger improvement was achieved by the control group. The training intervention decreased glucose fluctuations and occurrence of hypoglycaemic events in type 1 diabetes, while signs of mild myopathy found in the muscle of participants with type 1 diabetes only partially improved after training Improving muscle health by specific exercise protocols is of considerable clinical interest in therapeutic strategies for improving type 1 diabetes management and preventing or delaying long‐term complications. Abstract : Abstract figure legend The effect of type 1 diabetes on functional and molecular markers of skeletal muscle health in response to a training period and compared to healthy people. Ten people with type 1 diabetes and 10 healthy control subjects participated in a 12‐week, high‐intensity, combined exercise training programme. Muscle biopsies were collected before and after the training. At baseline, participants with type 1 diabetes exhibited a reduced level of mitochondrial DNA, proteins related to the oxidative phosphorylation (OXPHOS) system and reduced telomere length compared to control. These changes were detectable despite the two groups being comparable for body composition and functional measurements. The training programme improved glycaemic control but people with type 1 diabetes had a reduced adaptation in muscle force and aerobic capacity compared to control. The training period only partially improved the diabetes‐induced alterations of skeletal muscle health. Created with BioRender.com.